Desain Kurikulum Saintifikasi Pada Matapelajaran Pendidikan Agama Islam di Sekolah Dasar Al Azhar Syifa Budi Solo - Viki Bayu Mahendra; Siti Choiriyah (AL MURABBI, 2022)
This study is motivated by the emergence of the phenomenon of moral degradation in elementary school children, which is expected to have a negative impact in the future. Al Azhar Syifa Budi Solo Elementary School is a national school with an international perspective that uses a spiritualization and education science system. The purpose of this research is to determine (1) the design of the scientific curriculum for the education subjects of Al Azhar Syifa Budi Solo Elementary School, and (2) the implementation of the scientific curriculum for Islamic religious education subjects at Al Azhar Syifa Budi Primary School Solo. The research method used in this study was qualitative descriptive research. The research was conducted at Al Azhar Syifa Budi Elementary School in Solo, from June to August 2021. In the field of curriculum, the subjects were members of the central Al Azhar Syifa Budi Balitbang and deputy principal of Al Azhar Syifa Budi Solo Elementary School. Daily implementers, principals, and PAI subject teachers at Al Azhar Syifa Budi Elementary School Solo were the study's informants. Data collection methods rely on observation, interviews, and documentation. Meanwhile, triangulation technique is used for data validity. Data collection techniques, data reduction, data presentation, and verification are all used in the data analysis technique. The study's findings indicate that: (1) the scientific curriculum in Islamic religious education subjects at Al Azhar Syifa Budi Elementary School Solo is designed to use the scientific method approach, namely using a scientific or scientific approach in religious learning (Qur'an, hadith, or wisdom from both). (2) At Al Azhar Syifa Budi Elementary School, the scientific approach to Islamic religious education subjects is implemented both inside and outside the classroom. (3) Students are supervised through control books such as the iqro report book, obligatory prayer implementation report book, prayer and tadarus report book, general skill requirement book (SKU) in the religious field, and link book in order to support and assist the school in overseeing the program that has been created.